How to Properly Measure a Current-Voltage Relation?—Interpolation vs. Ramp Methods Applied to Studies of GABAA Receptors - Yelhekar, Tushar D.; Druzin, Michael; Karlsson, Urban; Blomqvist, Erii; Johansson, Staffan (Frontiers in Cellular Neuroscience, 2016)
The relation between current and voltage, I-V relation, is central to functional analysis of membrane ion channels. A commonly used method, since the introduction of the voltage-clamp technique, to establish the I-V relation depends on the interpolation of current amplitudes recorded at different steady voltages. By a theoretical computational approach as well as by experimental recordings from GABAA-receptor mediated currents in mammalian central neurons, we here show that this interpolation method may give reversal potentials and conductances that do not reflect the properties of the channels studied under conditions when ion flux may give rise to concentration changes. Therefore, changes in ion concentrations may remain undetected and conclusions on changes in conductance, such as during desensitization, may be mistaken. In contrast, an alternative experimental approach, using rapid voltage ramps, enable I-V relations that much better reflect the properties of the studied ion channels.